Neurodevelopment in children born to women exposed to pesticides during pregnancy - William Nelson Mwakalasya; Simon Henry Mamuya; Karim Manji; Bente Elisabeth Moen; Aiwerasia Vera Ngowi (PLoS ONE, 2025)
The global rise in pesticide use, particularly across Africa, raises concerns about maternal occupational exposure during pregnancy and its potential impact on child neurodevelopment. This study examined associations between self-reported maternal pesticide exposure during pregnancy and neurodevelopmental outcomes in children aged 4–6 years. A cross-sectional design was implemented, comprising 432 mother–child pairs from three horticulture-intensive regions in Tanzania. Maternal exposure was assessed through structured interviews, focusing on activities during pregnancy such as pesticide spraying, weeding, and handling contaminated clothing. Children’s neurodevelopment was evaluated using the International Development and Early Learning Assessment (IDELA), which measures motor skills, literacy, numeracy, social–emotional development, and executive function. Linear regression analyses revealed that children of mothers who reported pesticide spraying during pregnancy scored significantly lower in social–emotional (β = –6.813, 95% CI: –11.53 to –2.096, p = 0.005) and executive function (β = –9.317, 95% CI: –16.007 to –2.627, p = 0.006) domains. Overall, children achieved the highest mean scores in fine and gross motor skills (62.11 ± 19.3) and the lowest in executive function (43.97 ± 24.3). Age-related differences were also observed, with six-year-olds consistently outperforming younger children across all developmental domains. These findings suggest an association between maternal pesticide exposure during pregnancy and adverse neurodevelopmental outcomes in offspring. Given that exposure data were self-reported, results should be interpreted cautiously. Nevertheless, the study underscores the urgent need for comprehensive risk assessments incorporating objective exposure measurements, particularly in horticultural settings where women of reproductive age represent a substantial proportion of the workforce.